A malectin‐like receptor kinase regulates cell death and pattern‐triggered immunity in soybean - Wang, Dongmei (EMBO Rep, 2020)
Plant cells can sense conserved molecular patterns through pattern recognition receptors (PRRs) and initiate pattern‐triggered immunity (PTI). Details of the PTI signaling network are starting to be uncovered in Arabidopsis, but are still poorly understood in other species, including soybean (Glycine max). In this study, we perform a forward genetic screen for autoimmunity‐related lesion mimic mutants (lmms) in soybean and identify two allelic mutants, which carry mutations in Glyma.13G054400, encoding a malectin‐like receptor kinase (RK). The mutants exhibit enhanced resistance to both bacterial and oomycete pathogens, as well as elevated ROS production upon treatment with the bacterial pattern flg22. Overexpression of GmLMM1 gene in Nicotiana benthamiana severely suppresses flg22‐triggered ROS production and oomycete pattern XEG1‐induced cell death. We further show that GmLMM1 interacts with the flg22 receptor FLS2 and its co‐receptor BAK1 to negatively regulate flg22‐induced complex formation between them. Our study identifies an important component in PTI regulation and reveals that GmLMM1 acts as a molecular switch to control an appropriate immune activation, which may also be adapted to other PRR‐mediated immune signaling in soybean.